Biosynthesized magnetite-perovskite (XFe2O4-BiFeO3) interfaces for toxic trace metal removal from aqueous solution. Issue 17 (1st December 2018) - Nie, Jianan; Bian, Liang; Gu, Xiaobin; Jiang, Xiaoqiang; Dong, Hailiang; Song, Mianxin; Dong, Faqin; Zhang, Limin; He, Huichao; He, Ping; Belzile, Nelson; Chen, Yuwei; et al.
Abstract: X-modified magnetite (XFe2 O4 ; X = Cr, Mn, Fe, Co or Ni) was synthesized from goethite reduction, and inserted into the Fe-vacancy of perovskite (BiFeO3 ), via microbial Fe 3+ →Fe 2+ reduction by Shewanella (e.g. Shewanella oneidensis MR-1 and Shewanella putrefaciens CN32). We demonstrated that the average adsorption intensities of nine toxic trace metals (Cr 3+, Mn 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, Cd 2+, Pb 2+, and Hg 2+ ), in Freundlich mode were 8.29–10.79 multiples higher than that in Langmuir mode, being more competitive than previously reported values. The fluorescence quenching is attributed to the orbital hybridization of molecular oxygen activation and trace metal (M) ions, which weakens the X 2+ -O-Fe 3+ -O-(Fe 3+ ) coupling orbital. In addition Shewanella putrefaciens CN32 creates more oxygen vacancies to modify Ni↓-Fe↓-O↑ d*-p hybridized orbitals for enhancing the local spin-orbit coupling with Cd-4d 10 . This design idea can be extended to other direct biosynthetic magnetite-perovskite as highly efficient toxic trace metal removal agents.